Analysis on Students’ Perceptions Towards Online Teamwork During Covid-19 Pandemic: A Case Study in UTHM - Rozali, Nur Hazwanie; Che Him, Norziha (Enhanced Knowledge in Sciences and Technology, 2023)
Virtual teams consist of at least one online team member and depend on most of technology for task communication and coordination. This study investigates the perceptions of online teamwork among UTHM students during Covid-19 pandemic. The main purposes of this research to identify the effectiveness of online teamwork among UTHM students during Covid-19 and also to investigate if that online teamwork during a pandemic leaves a good or bad impact towards UTHM students. The study successfully collected 140 respondents among students of Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh and Parit Raja Campus. The Chi-Square analysis, and logistic regression as two methods that have been used in this study. The research shows that online teamwork was a prevalent method of collaboration among students during the Covid-19 pandemic, with many finding it convenient and mainly used for academic purposes. A statistically significant relationship was found between online teamwork and the effectiveness of collaboration among students. Online teamwork was found to have a positive impact on language skills, social skills, and the ability to learn from others. Overall, online teamwork can be an effective and beneficial way for students to collaborate and improve their skills during a pandemic.